Perbandingan Metode SAW dan Profile Matching Pada Pemilihan Rumah Tinggal: Studi Kasus: Perumahan Depok - Sunarti, Sunarti; Sundari, Jenie (Universitas Nusantara PGRI Kediri, 2018)
Convenient place, strategic, cool and affordable price is the dream of every person to be home. This research is conducted on housing in Depok City area with the name of Grand Depok City, Telaga Kahuripan, Maharaja, Sawangan Permai and Pesona Kayangan by using price, location, mortgage, facility, house type and initial payment by comparing two methods Supporting system of decision namely SAW and Profile Matching. The method is a method that the end result of the formation of the calculation process. The results of the comparison of the two methods are to produce the same chosen alternative, so that both methods can be applied to assist decision making in house selection in Depok